PENGARUH IKLAN POLITIK TERHADAP PERILAKU MEMILIH MASYARAKAT PENGRAJIN TAS DAN SEPATU PADA PILKADA SIDOARJO 2010 - Fadilah, Nur (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This study tries to reveal the influences of political advertising on voting behavior by making the community of bags and shoes craftsmen as objects. The district of Tanggulangin with all the complexity was taken as the field of research. The data obtained from observation, interviews, questionnaires and documentation. The researchers finally has concluded that the types of political advertising usually used were political ID and billboards, stickers and newspapers. The finding of study showed that there was a strong influence between political advertising in the mass media on the public voting behavior.